Fenomena Gender dalam Penyiaran dan Perkembangannya - Winda Kustiawan; Try Akhmal Hidayat (Maktabatun: Jurnal Perpustakaan dan Informasi, 2022)
In broadcast media, the phenomenon of gender is an issue that is often debated, especially in the media. This is important to discuss because the broadcast media has quite influenced the perspective and mindset of the community regarding gender issues in society. The wide coverage of the media will certainly persuade many people to see issues that are often debated in society. This study aims to find out how the phenomenon of gender in broadcasting and its development by the media. This research uses descriptive qualitative research methods with data collection methods through media content analysis and literature studies by searching for data through books and journals that support this research. The results of this study conclude that the media has a great influence in broadcasting issues about gender phenomena in society. The depiction by the media is also now a standardization of society in determining and shaping gender roles.